Constructing an instrument for to measure attitude towards distance learning and applying it to a sample of the students of Mu'tah University - Al-Mawadeh, Hanin Lafi Zal; Al-Mawadeh, Nofah Sameh Kamel (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed at constructing an instrumentfor to measur attitude towards distance learning and applying it to a sample of the students of Mu'tah University, and the study sample consisted of (500) students from the University of Mu'tah, who were chosen through the available sample style in light of the Korona pandemic. The measurement tool, which was formed in its final form of (46) paragraphs distributed over five dimensions. The results indicated that there are statistically significant differences in the direction towards learning from a distance attributed to the college's variable and for the benefit of humanitarian colleges. The results also showed that the connotations of the sincerity and stability of the direction measurement tool towards learning from a dimension was high. The results also indicated that students' attitudes towards learning from a distance at Mu'tah University were positive and moderate and that there are no statistically significant differences in the direction towards learning from a distance attributed to the gender variable. In light of this study, the two researchers reached a set of recommendations, including: the search for new statistical methods to know the indications of the sincerity and stability of the learning measurement tool.
Keywords: the attitude towards distance learning; students of Mu'tah University